2020
DOI: 10.1016/j.jceh.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia in Cirrhosis: Fallout on Liver Transplantation

Abstract: Background: Liver transplantation (LT) is a game changer in cirrhosis. Poor muscle mass defined as sarcopenia may potentially upset the LT scoreboard. Aim: To assess the prevalence and impact of sarcopenia on the intraoperative and early postoperative outcomes in Indian patients undergoing LT. Methods: Pre LT, single-slice routine computed tomography images at L3 vertebra of 115 LT recipients were analyzed, to obtain crosssectional area of six skeletal muscles normalized for height in m 2skeletal muscle index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 40 publications
(40 reference statements)
1
43
0
Order By: Relevance
“…The most commonly used cutoff points for the SMI in sarcopenia studies are 52.4 cm 2 /m 2 for men and 38.5 cm 2 /m 2 for women, which were found to be associated with mortality in obese patients with solid tumors [31]. These sex-specific cutoff values have also been widely used in sarcopenia studies in patients with cirrhosis and have been shown to be associated with high mortality [13,[32][33][34][35][36][37]. Martin et al developed another cutoff value derived from cancer patients, which was stratified by body mass index, and sarcopenia based on this cutoff value was associated with increased mortality (L3 SMI ≤ 53 cm 2 /m 2 for men and ≤41 cm 2 /m 2 for women with a BMI ≥ 25 kg/m 2 and L3 SMI ≤ 43 cm 2 /m 2 for patients with a BMI < 25 kg/m 2 ) [38].…”
Section: Skeletal Muscle Measurement By Ctmentioning
confidence: 99%
“…The most commonly used cutoff points for the SMI in sarcopenia studies are 52.4 cm 2 /m 2 for men and 38.5 cm 2 /m 2 for women, which were found to be associated with mortality in obese patients with solid tumors [31]. These sex-specific cutoff values have also been widely used in sarcopenia studies in patients with cirrhosis and have been shown to be associated with high mortality [13,[32][33][34][35][36][37]. Martin et al developed another cutoff value derived from cancer patients, which was stratified by body mass index, and sarcopenia based on this cutoff value was associated with increased mortality (L3 SMI ≤ 53 cm 2 /m 2 for men and ≤41 cm 2 /m 2 for women with a BMI ≥ 25 kg/m 2 and L3 SMI ≤ 43 cm 2 /m 2 for patients with a BMI < 25 kg/m 2 ) [38].…”
Section: Skeletal Muscle Measurement By Ctmentioning
confidence: 99%
“…And lastly, there have been no studies from the Indian sub-continent in this space. This is relevant as muscle mass and function are known to vary considerably by ethnicity (17)(18)(19)(20), limiting the generalizability of North American studies to the Indian population. Accordingly, in an outpatient cohort of patients from the Indian sub-continent, this study was designed to address these knowledge gaps.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the cutoffs (28.15 cm 2 /m 2 in men and 26.0 cm 2 /m 2 in women by taking below the 5th percentile) of SMI derived by us after analyzing the preoperative computerized tomography (CT) scans of 110 healthy Indian liver donors. We believe that using these cutoffs, the prevalence of sarcopenia among Indian patients with end stage liver disease (ESLD) presenting for LT would be much lower than the 48% described by Vaibhaw et al 1 Because of the use of higher cutoffs, they found no difference in mortality between sarcopenic and non-sarcopenic patients although SMI stood out as an independent predictor of posttransplant mortality on multivariate analysis in their study.…”
mentioning
confidence: 65%
“…We read with interest the article by Vaibhaw et al 1 which has described a high post-liver transplant morbidity in recipients with sarcopenia on the basis of skeletal muscle index (SMI) cutoffs of <52.4 cm 2 /m 2 for men and <38.5 cm 2 / m 2 for women. They demonstrated that almost half (48%) of the patients who underwent liver transplant (LT) at their center over a period of two years had sarcopenia.…”
mentioning
confidence: 99%